La institucionalización de normas según el denominador común más bajo: la norma antigolpista en las Naciones Unidas - Tansey, Oisín (El Colegio de México A.C., 2019)
After the end of the Cold War, states and international organizations increasingly adopted a new “anti-coup norm.” However, this norm has evolved unevenly, and has never been universally embraced or consistently enforced. This article examines the uneven evolution of the anti-coup norm by tracing its fate within the United Nations system. It shows how member states have sought to retain discretion in how they respond to individual coup cases, and how, in response, UN officials within the Secretariat sought to pursue norm institutionalization by changing the UN’s internal rules and procedures for dealing with coup countries. In doing so, they pursued “lowest common denominator” norm institutionalization, which involves seeking to achieve the highest level of institutionalization that is achievable, even if it means aiming for a lower level of progress than norm promoters would ideally like.